2014
DOI: 10.5301/ijao.5000315
|View full text |Cite
|
Sign up to set email alerts
|

Septic Shock Secondary to β-hemolytic Streptococcus-induced Necrotizing Fasciitis treated with a Novel Cytokine Adsorption Therapy

Abstract: This is the first report of the clinical application of CytoSorb hemoadsorption in combination with a CRRT in a patient with septic shock. CytoSorb as described was able to significantly reduce IL-6 plasma levels and decrease vasopressor need while no adverse and device-related events occurred. CytoSorb seems to be an interesting and safe extracorporeal therapy to stabilize and bridge septic patients to surgery or recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 19 publications
5
54
0
5
Order By: Relevance
“…Experimental and clinical studies have widely demonstrated their ability to modulate inflammatory mediators in septic shock [14][15][16]; preliminary case reports in systemic inflammatory response and septic shock [12,13], as well as recent experiences [17][18][19], have shown that the sorbent also reduces bilirubin and bile acids. This combined action may be helpful in supporting liver dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and clinical studies have widely demonstrated their ability to modulate inflammatory mediators in septic shock [14][15][16]; preliminary case reports in systemic inflammatory response and septic shock [12,13], as well as recent experiences [17][18][19], have shown that the sorbent also reduces bilirubin and bile acids. This combined action may be helpful in supporting liver dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, sorbents have been used to eliminate industrial, pharmacological, or endogenous toxins such as bilirubin or porphyrines [11, 12]. Several new sorbents specifically designed for particular diseases and target molecules to be removed have been proposed in the last years and applied in clinical trials [13-18]. …”
Section: Introductionmentioning
confidence: 99%
“…These devices either remove target molecules below a specific size, such as inflammatory cytokines [28], or are coated with ligands that bind and remove a specific type of PAMP, such as the use of Polymyxin B immobilized on hemofilters to remove endotoxin [20,29]. We recently reported the development of a microfluidic, dialysis-like therapeutic device for sepsis therapy or 'biospleen' that removes living pathogens and endotoxin from blood using magnetic nanoparticles coated with a genetically engineered form of the human opsonin, Mannose Binding Lectin, that lacks its complement fixation and coagulation domains, and is linked to an antibody Fc domain (FcMBL) [30].…”
Section: Introductionmentioning
confidence: 99%